To Determine the Frequency of Discontinuation of Post-Partum Intra Uterine Contraceptive Device (PPIUCD) within 3 Months and its Causes: Frequency of Discontinuation of PPIUCD - Mand, Qamar Zaman; Rashid, Madeeha; Mughal, Mawrah; Matloob, Iqra; Noreen, Asifa; Khurshid, Kiren; Usman, Muhammad (Pakistan Journal of Health Sciences, 2023)
Pakistan has a high fertility rate of 3.8 and a low contraceptive prevalence of 35%. Worldwide studies have shown that poorly spaced pregnancies have a negative impact on both the health of mothers and their children. Objective: To determine the frequency of early discontinuation of post-partum intra uterine contraceptive device within 3 months and its causes. Methods: A quantitative cross-sectional study was carried out at Services Hospital Obstetrics and Gynecology unit Lahore for a period of 6 months from 1st October 2022 to 31st March 2023. 236 pregnant women who underwent post-partum intra uterine contraceptive device insertion and agreed for a follow up were recruited after written consent. They were followed up by the researcher himself for 3 months. The data (age, parity, literacy, early discontinuation (yes/no) and factors for discontinuation i.e. side effects, discontinuation for their husband’s dislike or in-law’s opposition and desire for more children was recorded on a specially designed proforma. Results: The frequency of early discontinuation of IUCD was found in 51 (21.61%) patients. Among the causes, side effects (60.78%) was the main cause of discontinuation followed by discontinuation due to their husband’s dislike or in-law’s opposition (21.57%), desire for more children (5.88%) and myths (3.92%). Conclusions: This study concluded that about one third of the patient’s frequency of early discontinuation of IUCD was 21.61% with side effects being the main cause of discontinuation followed by discontinuation due to their family pressure